Congenital giant fibroepithelial polyp of the scrotum in an infant: the first case report from China - Zhanghuang, Chenghao; Hang, Yu; Ji, Fengming; Long, Na; Yao, Zhigang; Li, Li; Yang, Zhen; Tang, Haoyu; Zhang, Kun; Wu, Chengchuang; Xie, Yucheng; Yan, Bing (Frontiers in Pediatrics, 2023)
Giant fibroepithelial polyp (FP) of the scrotum in infants is a rare disease. We reported the first case of FP in China. The child was only 9 months and 12 days old and was admitted to the hospital due to rapid growth and rupture of the scrotal mass. The patient underwent scrotal exploration under general anesthesia, and the mass was cystic-solid with clear boundaries. The tumor did not invade the sarcolemma of the scrotum and testicular tissue. The intraoperative pathological frozen section tended to be benign, and the scrotum's tumor and subcutaneous pedicle tissue were removed entirely after 0.5cm from the boundary of the mass. The operation was successful. The mass was confirmed as FP by postoperative pathology. 6 months after the operation, the incision healed well without recurrence. This case report has a detailed diagnosis and treatment process and adequate examination results. It can provide a reference for diagnosing and treating FP in infants and reduce the risk of misdiagnosis and mistreatment.